Quality of coffee plant seeds produced under different planting densities and hydric regimes - Pedroso, Thiago Queiroz; Scalco, Myriane Stella; Carvalho, Maria Laene Moreira de; Resende, Carlos Alberto de (Coffee Science - ISSN 1984-3909, 1970)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The water availability during the seed formation of various species is one of the factors that determine their physiological quality. For species such as coffee, seed quality can ensure the production of vigorous and healthy plants, essential to the formation of productive crops. To assess the quality of coffee (Coffea arabica, L.) seeds cultivar Rubi MG-1192, grown under two planting densities (2500 plants ha-1 and 5000 plants ha-1) and submitted to three drip irrigation systems (control, 20 kPa and 100 kPa) in the course of three harvests (first, second and third years of production) a completely randomized experimental block design was used, in a split-plot with four replications. The seeds were evaluated as to their physical and physiological quality through tests of germination, tetrazolium, bulk electrical conductivity, seedling emergence and percentage of “moca” and damaged seeds . The most vigorous seeds were obtained within the plant density of 5000 plants ha-1 regardless of the season and the irrigation system. There is an effect of planting density and water availability on seed quality, and this effect is variable depending on climatic conditions, productivity and age of the plant.